Makna Zikir Bagi Jemaah Tarekat Naqshabandīyah Khālīdīyah Majelis Pengkajian Tauhid Tasawuf Indonesia di Kota Gorontalo - Rahmawati Rahmawati; Kasim Yahiji; Mustakimah Mustakimah (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
This article attempts to elaborate the existence of dhikr along with its meaning performed and hold by the members of the Majelis Pengkajian Tauhid Tasawuf Indonesia under the auspices of the Tarekat Naqshabandīyah Khālidīyah in Gorontalo City. The study indicates that dhikr is a substantially mandatory ritual that must be performed by the followers of the tarekat. At this point, they interpret the meaning of dhikr within various arguments. The tarekat members who reached what so-called the level of tawhīd ‘aqīdah argue that dhikr is an important matter which brings about positive energy and leads its performers to discover true religious spirituality. They believe that positive energy becomes a significantly determinant factor and it has relevance to solve the problems of daily life. On the other side, the tarekat members who have reached the level of tawḥīd ṣūfī interpret dhikr as a spiritual obligation that orients its performers to lovingness and intimacy with God. To the urban society of Gorontalo dhikr is viewed as a mindset that emphasizes that within spiritually sacred realm, on one hand, dhikr provides a positive indication that is coherently compatible with the profane reality of their life on the other.